Thrombolysis choise for pulmonary embolism treatment - A. S. Nikonenko; A. A. Nikonenko; S. A. Matvieiev; V. V. Osaulenko; S. Y. Nakonechniy (Ukrainian Journal of Cardiovascular Surgery, 2016)
Pulmonary embolism is a complex clinical problem, which is often cause of acute heart failure, death and disability of patients.An aim of the study was to analyze the results of the various methods of treatment of PE to evaluate the effectiveness of therapy.The results of treatment of 349 patients with pulmonary embolism, whom using thrombolysis and anticoagulation therapy were analyzed. There was found high efficiency of thrombolytic therapy for massive and submassive pulmonary embolism.